Computer games and software engineering - Cooper, Kendra M. L.; Scacchi, Walt (Chapman & Hall/CRC innovations in software engineering and software development series ;, 2015)
The book explores the use of games in software engineering education extensively. It also covers game software requirements engineering, game software architecture and design approaches, game software testing and usability assessment, game development frameworks and reusability techniques, and game scalability infrastructure, including support for mobile devices and web-based services.